Penerapan Building Performance sebagai Usaha Menciptakan Kenyamanan Termal - Salim, Victor Christian; Kusumowidagdo, Astrid (Universitas Ciputra Surabaya, 2021)
Indonesia is a large and rich country, predicted to be number 6th in the world economy by 2023. This is of course followed by the development of business sectors in the country, especially creative industries including the architectural design industry. The growing competition in the world of architecture with the number of firms that have sprung up has encouraged business performer in search for “added value” that can make their services receive more attention from the public. One thing that is appealing is green architecture, especially building performance that offers environmental friendly and energy-saving options. Aspects of concern in building performance include energy efficiency itself, productivity, and comfort. For many people energy efficiency is often associated with retrenchment, that reduce comfort, one of which is thermal comfort. In fact, building performance works simultaneously. Considering 3 aspects that concern the building performance, one of them is comfort, thermal comfort is one of the concerns. In fact, many building performance strategies can be offered and applied to architectural designs that improve heat management, especially heat loss such as shade and ventilation / ventilation that can handle this. With the right strategy, it is not only the energy savings we get, the comfort of the residents themselves can be maintained.